Effect of Dietary Supplementation of the Combination of Gallic and Linoleic Acid in Thigh Meat of Broilers - Lee, Kyung Haeng (Asian-Australasian Association of Animal Production Societies (AAAP) and Korean Society of Animal Science and Technology (KSAST), 2012)
This study was performed to investigate the combined effect of dietary supplementation of gallic and linoleic acid (GL) on the antioxidative effect and quality of thigh meat from broilers. Broilers received 3 dietary treatments: i) commercial finisher diet (control), ii) 0.5% GL (gallic:linoleic acid = 1 M:1 M), and iii) 1.0% GL during the 22 to 36 d. The pH value of broiler thigh meat was increased by GL supplementation. Water holding capacity of the thigh meat was enhanced by the 1.0% dietary GL supplementation. Antioxidative effect (total phenolic content, DPPH radical scavenging activity, ABTS(+) reducing activity, reducing power, and TBARS value) in the thigh from the broilers improved significantly with 1.0% GL. Linoleic acid and docosahexaenoic acids were higher in the broilers fed both levels of dietary GL. However, volatile basic nitrogen content and microbiological quality was not shown to be different between control and treated group. Results indicate that 1.0% dietary supplementation of GL can improve the antioxidant activity of broiler thigh meat and may enhance the meat quality.